Behavior of Strip Footing/s above Void in Sandy Soil - Benbouza, Assma; Mansouri, Tarek; Abbeche, Khelifa (Engineering, Technology & Applied Science Research, 2023)
This paper presents a numerical study that utilizes finite element analysis under the plain strain condition performed on sand with isolated strip footing and two closely spaced strip footings above a continuous void. The Bearing Capacity Ratio (BCR) and the efficiency factor ζγ were introduced to determine the effect of the void on the ultimate bearing capacity of footing/s. The influence of various parameters including spacing (S/B) (i.e. edge to edge) between the two interfering footings along with the location and the shape of the void were studied. In general, the results indicate that the presence of a void reduces the bearing capacity and affects the performance of footing/s and there is a critical value of S/B beyond which the effect of the void on the bearing capacity of the interfering footings becomes negligible.